Changes in eating attitudes, body esteem and weight control behaviours during adolescence in a South African cohort. - Tabither M Gitau; Lisa K Micklesfield; John M Pettifor; Shane A Norris (PLoS ONE)
Failure to consume an adequate diet or over consumption during adolescence can disrupt normal growth and development, resulting in undesirable weight change. This leads to an increase in unhealthy weight control practices related to eating and exercise among both adolescent girls and boys to meet the societal 'ideal' body shape. This study therefore aims to examine the longitudinal changes in eating attitudes, body-esteem and weight control behaviours among adolescents between 13 and 17 years; and, to describe perceptions around body shape at age 17 years. A total of 1435 urban South African black and mixed ancestry boys and girls, who had data at both age 13 and 17 years from the Birth to Twenty cohort were included. Data were collected through self-administered questionnaires on eating attitudes (EAT-26), body esteem and weight control behaviours for either weight loss or muscle gain attempts. Height and weight were measured at both time points and BMI was calculated. Black females had a higher BMI (p<0.001) and an increased risk of developing eating disorders as well as significant increase in the prevalence of weight loss practices between the ages 13 and 17 years. At age 17 years both Mixed ancestry adolescents had lower body-esteem compared to black adolescents. The prevalence of possible eating disorders was 11% and 13.1% in early and late adolescents respectively. Males and females shared similar opinions on normal silhouettes being the 'best', 'getting respect' and being the 'happiest', while the obese silhouette was associated with the 'worst' and the 'unhappiest', and the underweight silhouette with the "weakest". Black females had a higher BMI and an increased risk of developing eating disorders. Adolescent females engaged more in weight loss practices whereas, males in muscle gain practices indicating that Western norms of thinness as the ideal are becoming more common in South Africa.